Penerapan Good Manufacturing Practices (GMP) melalui Pelatihan pada UMKM ”Omah Mente” Kota Malang untuk Meningkatkan Mutu dan Penguatan Daya Saing Produk Mente - Sri Handayani; Nonok Supartini; Farida Farida; Kgs Ahmadi; Sumarno Sumarno; Henny Leondro (Universitas Tribhuwana Tunggadewi Malang, 2025)
Omah Mente is an MSME that processes cashew nuts into fried cashew nuts and cashew cookies. The problem faced by Omah Mente is that the production process is still carried out manually and does not implement GMP due to a lack of knowledge about GMP and limited capital for technological innovation and GMP implementation. In the implementation of this community service activity, production technology innovation, socialization about GMP and training and mentoring on GMP implementation were carried out. The results of the community service program with the introduction of production technology increased production capacity from 2 kg to 7 kg. The implementation of GMP resulted in the production process being carried out according to good processing methods, resulting in clean, hygienic, and safe products. This increase in production has increased marketing through a consignment system at food stores in Malang City.ABSTRAKOmah Mente merupakan UMKM yang mengolah mente menjadi mente goreng dan kue (cookies) mente. Permasalahan yang dihadapi Omah mente adalah proses produksi masih dilakukan secara manual belum menerapkan GMP karena kurangnya pengetahuan tentang GMP dan keterbatasan permodalan untuk inovasi teknologi dan penerapan GMP. Pada pelaksanaan kegiatan pengabdian kepada masyarakat ini dilakukan inovasi teknologi produksi, sosialisasi tentang GMP dan pelatihan dan pendampingan penerapan GMP. Hasil program pengabdian kepada masyarakat dengan introduksi teknologi produksi meningkatkan kapasiats produksi dari 2 kg menjadi 7 kg. Penerapan GMP menghasilkan proses produksi telah berjalan menurut cara-cara pengolahan yang baik sehingga menghasilkan produk yang bersih, higienis, dan aman. Peningkatan produksi ini telah meningkatkan pemasaran melalui sistem konsinyasi pada toko ole-ole kota Malang